2006
DOI: 10.1208/aapsj080250
|View full text |Cite
|
Sign up to set email alerts
|

Endocannabinoid Signaling Directs Periimplantation Events

Abstract: An emerging concept in female reproduction is the role of endocannabinoids, a group of endogenously produced lipid mediators that bind to and activate cannabinoid receptors. Although adverse effects of cannabinoids in female reproduction have been implicated for years, the mechanisms by which they exert these effects remained elusive. With the identifi cation of cannabinoid receptors, endocannabinoid ligands, their key synthetic and hydrolytic pathways, and the generation of knockout mouse models for cannabino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 44 publications
1
14
0
1
Order By: Relevance
“…The regulation of ''AEA tone'' by FAAH has been proposed as an important event in the oviduct during early pregnancy (33), as well as in blastocyst activation (34) and implantation (35), but no hypotheses have been proposed in relation to such a process in oocyte maturation. Even so, it has been described that AEA concentration in human follicular fluid rises during oocyte maturation (15) and that the concentration is even higher in the oviduct than in follicular fluid (36).…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of ''AEA tone'' by FAAH has been proposed as an important event in the oviduct during early pregnancy (33), as well as in blastocyst activation (34) and implantation (35), but no hypotheses have been proposed in relation to such a process in oocyte maturation. Even so, it has been described that AEA concentration in human follicular fluid rises during oocyte maturation (15) and that the concentration is even higher in the oviduct than in follicular fluid (36).…”
Section: Discussionmentioning
confidence: 99%
“…For example, previous studies have demonstrated that cannabinoid signaling participates in sperm-egg fertilization, preimplantation development of embryos and their timely transport from the oviduct into the uterus, and embryo-uterine cross-talk during implantation and decidualization [52][53][54][55][56]. Opioid receptors and cannabinoid receptors are all belong to the G-protein-coupled receptors super families.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma AEA levels are maintained by the actions of the enzymes fatty acid amide hydrolase (FAAH) and N-acyl phosphatidylethanolamine phospholipase D (NAPE-PLD) and together with a putative, but yet undiscovered anandamide membrane transporter, constitute the major components of the 'endocannabinoid system' (Di Marzo 2008;Habayeb et al 2008a;Pacher et al 2006). All of these component parts of the endocannabinoid system have been demonstrated in rodent uteri (Paria et al 2001;Wang et al 2006bWang et al , 2007, suggesting that the endocannabinoid system is intimately involved in the physiology of mammalian reproduction. Also, in rodent models of early pregnancy, it has been demonstrated that the expression of FAAH and NAPE-PLD are modulated by circulating sex steroid hormones (Maccarrone et al 2000a) and by the presence of the blastocyst ) such that FAAH levels are increased and NAPE-PLD levels are decreased in the implantation site as compared to the nonimplantation site (Guo et al 2005;Maccarrone 2009), whilst at the same time elevated local anandamide levels are associated with detrimental effects on the mouse blastocyst (Sun and Dey 2008).…”
Section: Introductionmentioning
confidence: 99%